Audit Report Lag: An Empirical Investigation of the Effects of Audit Tenure, Solvency, and Firm Size - Sari, Wilda; Jaurino, Jaurino; Khasanah, Dini Afriani; Setiawan, Aris (Jurnal Akuntansi, 2025)
Purpose – Financial reviews are the ultimate end result of the accounting process, serving as a device to speak about financial activities that aid the sustainability of a company. Audit record lag is an essential indicator in assessing the effectiveness and transparency of a company's economic reporting process. This learns about targets to check out and empirically take a look at the impact of audit tenure, solvency, and company measurement on audit report lag. Design/methodology/approach – The lookup makes use of a quantitative method, with statistics from the Indonesia Stock Exchange. The populace in this learn about is manufacturing corporations in the Property Real Estate sub-sector. A pattern of 60 businesses used to be received with a statement length of 5 years, ensuing in a whole of 300 samples. The records have analyzed the usage of Eviews-13 software. Findings – The effects exhibit that audit tenure negatively impacts audit record lag, whilst solvency and association measurement have a high-quality impact on audit file lag. Research limitations/implications –This study is limited by the observation year and the data obtained, as the data was sourced solely from external sources. Keywords: Audit Report Lag, Audit Tenure, Firm Size, Solvency